Določanje stabilnosti skalometov, obremenjenih z valovanjem - Čehovin, Jerneja (Acta hydrotechnica, 2019)
We compare the Iribarren, Hudson, and Van der Meer methods for designing rock armour revetments and breakwaters using fictive but plausible wave parameters. The obtained results show relatively high discrepancy. The Hudson method requires elements of almost twice the weight of those calculated using the Irribaren method, and the difference in maximum wave resistance is between 20 and 30%. Compared to the Hudosn method, the duration of storms causing 5, 20 and 30% damage to rock armour designed using the Iribarren method is two-fold lower for the trunk and almost an order of magnitude lower for the head of the rock armour. We suggest that the designers choose a method upon thoughtful consideration of the structure's purpose and importance, and of potential damage due to the structure's either partial or complete collapse.
Keywords: Hudson method; Iribarren method; metoda Hudson; metoda Iribarren; metoda Van der Meer; rock armour; skalomet; stability; stabilnost; Van der Meer method